2021
DOI: 10.3390/diagnostics11040702
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Are Associated with Prognosis and Survival in Breast Cancer

Abstract: Dendritic cells (DCs) constitute a part of the tumour microenvironment, but we are still far from understanding their complex role in immune response to the tumour. This study aimed to investigate the density of DCs expressing CD1a, CD83, CD123, DC-LAMP3 (CD208) and DC-SIGN (CD209) in breast cancer. The correlations between DC density and molecular subtype of breast cancer, its hormone receptor status, spatial location and their associations with clinical and pathological prognostic factors were evaluated. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 40 publications
2
24
0
2
Order By: Relevance
“…We identified a large population of macrophages, including those associated with tumors (primary or liver mets) or with normal tissue (normal colon or liver). We also identified a number of other myeloid dendritic cell (DC) types, including BATF3+ DCs required for effector T cell trafficking and adoptive T cell therapy 25 , CD1c+ DCs which prime cytotoxic T cell responses 26 , Tumor-associated LAMP3+ DCs 27,28 , and LILRA4+ plasmacytoid dendritic cells 29 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified a large population of macrophages, including those associated with tumors (primary or liver mets) or with normal tissue (normal colon or liver). We also identified a number of other myeloid dendritic cell (DC) types, including BATF3+ DCs required for effector T cell trafficking and adoptive T cell therapy 25 , CD1c+ DCs which prime cytotoxic T cell responses 26 , Tumor-associated LAMP3+ DCs 27,28 , and LILRA4+ plasmacytoid dendritic cells 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, higher densities of CD1a+ DCs both in the stroma of primary invasive tumors and in LNs were associated with absence of nodal metastases and good prognosis [ 22 , 23 ]. Similarly, in our recent study we showed that a higher density of intratumoral CD1a DCs was associated with longer progression-free survival in BC patients [ 16 ]. These would support the hypothesis that higher levels of DCs evoke functional anti-cancer responses [ 22 ].…”
Section: Discussionmentioning
confidence: 61%
“…Recently we have shown that the content of respective DCs subtypes in BC tumors differs according to BC molecular subtype and clinicopathological features [ 16 ]. In this study, we investigated the densities of several DC populations in SLNs of invasive breast cancer patients with respect to the size of nodal metastasis and other prognostic parameters in this malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with their anti-tumor potentials, a higher density of tumor-infiltrating cDCs is associated with a better prognosis for patients with various tumor types [ 35 37 ]. Here we evaluated the anti-tumor activities of several DC-targeting chemokines in parallel to explore the possibility of using them for immunotherapy.…”
Section: Discussionmentioning
confidence: 95%